Resducational kit the development of an electronic quiz board that test engineering students knowledge on resistors concept in electrical circuit - Mohd Ab Halim, Mohd Firdaus; Mohd Nor, Abdul Muim; Badari, Ahmad Al-Baihaqi; Zainal Abidin, Amar Faiz; Kadiran, Kamaru Adzha; Adam, Asrul; Mohamad, Syahrul Hisham; Harun, Mohamad Haniff (Blue Eyes Intelligence Engineering & Sciences Publication (BEIESP), 2019)
The concept of basic electrical circuit has been covered in most engineering field especially electrical and electronic engineering via Fundamental of Electrical Circuit subject. One of the topic is to test student knowledge on calculation on the combinatorial resistors connection which can be either in series, parallels or combination of both. This can be done by theoretical calculation or hands-on assembling the circuit. This educational kit attempts to bridge the gap between theory and real-time hands-on for the circuit connection. The kit will give questions by providing the desired resistors output while the students need to do the connection base on the available resistors values in order to obtain the desired output resistor. The educational kit will deliverer the answer once the connection is successfully constructed. The kit is developed using Arduino Uno Microcontroller with other components such as LCD, LED, keypad, buzzer and resistors. This paper explains the procedure required in developing the prototype and testing being done to verify the functionality of the proposed kit.